Transferability and reproducibility of the EpiSkin™ Micronucleus Assay. (6th September 2022) - Chen, Lizao; Huang, Fang; Kei, CaiChun; Zhang, Jinsong; Sang, Jing; Yang, Ying; Kuang, Rong; Xiong, Xikun; Li, Qing; Liu, Yanfeng; Qin, Qin; Zhao, E; et al.
Abstract: A novel in vitro 3D micronucleus assay was developed in China using the EpiSkin™ 3D human skin model. This EpiSkin™ Micronucleus Assay showed good predictivity and reproducibility during internal validation and is expected to contribute to in vitro genotoxicity testing as a follow-up for positive results from 2D micronucleus assay. Having developed the assay in one laboratory, further work focused on the transferability and inter-laboratory reproducibility in two additional Chinese authority laboratories (Guangdong Provincial Center for Disease Control and Prevention and Zhejiang Institute for Food and Drug Control). Formal training was provided for both laboratories, which resulted in good transferability based on the results of two positive compounds, such as mitomycin C and vinblastine. Independent experiments were then performed, and inter-laboratory reproducibility was checked using 2-acetylaminofluorene, 5-fluorouracil, 2, 4-dichlorophenol, and d -limonene. The dose-responses of the positive control chemical, mitomycin C, were similar to those of the developing laboratory, and all test chemicals were correctly classified by all laboratories. Overall, there was a good transferability as well as intra- and inter-laboratory reproducibility of the EpiSkin™ Micronucleus Assay. This study further confirmed the assay's robustness and provided confidence to enter following validation stages for scientific acceptance.